Utilization of Technology in Human Resource Management Optimizing Efficiency and Productivity in the Digital Era - Abdus Salam; Munawir Munawir (International Journal of Management Science and Information Technology, 2024)
This research aims to explore the use of technology in human resource management (HR) to optimize efficiency and productivity. In this digital era, technology has become a crucial component in various aspects of HR management, from recruitment, training, performance evaluation, to employee data management. By using a case study approach on several companies that have implemented technology in their HR management processes, this research found that technology not only speeds up the administrative process, but also increases accuracy and consistency in decision making. Additionally, the use of HR management information systems (HRIS), cloud-based applications, and data analytics tools have enabled companies to monitor and manage employee performance in real-time. The research results show that the integration of technology in HR management can increase operational efficiency, reduce costs, and increase employee productivity and satisfaction. Thus, companies that invest in HR management technology are expected to gain a significant competitive advantage.